2021
DOI: 10.3389/fncel.2021.710481
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Mediate Inflammatory Injury and Aggravate Neurological Impairment in Experimental Subarachnoid Hemorrhage Through Microglial PAR-2 Pathway

Abstract: Subarachnoid hemorrhage (SAH) is a devastating cerebrovascular disease with high mortality and disability. Aberrant neuroinflammation has been identified as a critical factor accounting for the poor prognosis of SAH patients. Mast cells (MCs), the sentinel cells of the immune system, play a critical in the early immune reactions and participate in multiple pathophysiological process. However, the exact role of MCs on the pathophysiological process after SAH has not been fully understood. The current study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…The inflammatory response is an important step in EBI, which is induced by neuronal necrotic products and hemoglobin degradation products, and stimulates microglia activation after SAH [20]. The activated microglia amplify the inflammatory response, the principle macrophages of the central nervous system, releasing various inflammatory factors and chemokines that further promote neuronal damage [21]. Abundant evidence suggests that microglial activation and the subsequent neuroinflammatory response participates in EBI [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response is an important step in EBI, which is induced by neuronal necrotic products and hemoglobin degradation products, and stimulates microglia activation after SAH [20]. The activated microglia amplify the inflammatory response, the principle macrophages of the central nervous system, releasing various inflammatory factors and chemokines that further promote neuronal damage [21]. Abundant evidence suggests that microglial activation and the subsequent neuroinflammatory response participates in EBI [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…82 It has been suggested that mast cells play a pivotal role in early responses to aneurysm rupture by organizing the microglial response. 83 After local mast cells recognize blood-derived toxins, they rapidly degranulate and secrete tryptase, which binds to the Protease-activated receptor 2 (PAR-2) receptor on microglia, activating microglia and promoting the secretion of TNF-α, IL-1β, and IL-6. 83 Microglia then communicate with additional peripheral leukocytes.…”
Section: Microglia In Early Brain Injurymentioning
confidence: 99%
“…83 After local mast cells recognize blood-derived toxins, they rapidly degranulate and secrete tryptase, which binds to the Protease-activated receptor 2 (PAR-2) receptor on microglia, activating microglia and promoting the secretion of TNF-α, IL-1β, and IL-6. 83 Microglia then communicate with additional peripheral leukocytes. Chemokines produced by microglia recruit neutrophils and monocytes from the periphery that transmigrate through the compromised BBB and enter the CNS.…”
Section: Microglia In Early Brain Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…MCs secrete neuropeptides CRH and Substance P (SP), which activate microglia in the brain to generate IL-1 and the chemokines CXCL8 (34). In fact, MCs cross-talk with microglia by releasing histamine and tryptases which induce the secretion of pro-inflammatory cytokines in MCs (35).…”
Section: Introductionmentioning
confidence: 99%